Teatr szkolny w pracy nauczyciela polonisty. Wybrane zagadnienia - Sakowski, Bogdan (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2003)
This publication aims to familiarize Polish Language teachers with various issues connected with the Theatrical Education in Schools. Part 1 is an attempt to define the set role of a School Theatre Supervisor (what should be emphasized here is that the teacher’s knowledge of the subject, set designing skill, and also acting and directing skill and his/her knowledge of the pupil’s psyche at different stages in the development of an young man). Part 2 deals with the Theatrical Education as a part o f Polish language lessons, set in the early 21" century Polish reality (extracts from interesting theatre lessons, dramatic elements in the lesson, activities in the theatre lessons and theatre-journalism classes). Part 3 is a proposition of how to organize work in the school drama theatre (a suggestion on practice and methodology exposing various advantages gained through the school theatre activities).